Criteria for the efficiency of enterprise management in the framework of digital transformation - S. K. Kochina; E. D. Schetinina (Вестник университета)
The purpose of this article is to describe the essence and principles of a new methodological approach to the enterprise management system analysis in the context of digital transformation. The approach proposed by the authors is based on the key criteria for the effectiveness of any economic system management in the context of digital changes. The identified criteria for the effectiveness of management include such aspects as the enterprise digital transformation strategy development, which does not contradict the general course of development; the involvement of qualified employees in the field of digital management; ensuring the motivation of personnel to implement digital transformation; the introduction of a special modular digital platform that combines the necessary technologies, techniques; conducting systematic monitoring of the implementation of transformational tasks and goals. In this study, the authors used the method of theoretical generalization and comparison, scientific abstraction, logical, induction and deduction methods, etc. As a result of the study, it was concluded that it is expedient to apply the proposed methodological approach to the analysis of enterprise management by taking into account and evaluating the criteria for management effectiveness in the context of digital transformation, as well as calculating the integral index.